Identification of Rich Oil-Protein and Disease Resistance Genotypes in Soybean [Glycine max (L.) Merrill] - Uikey, Shivani; Sharma, Stuti; Amrate, Pawan K.; Shrivastava, M. K. (International Journal of Bio-resource and Stress Management, 2022)
A study was undertaken on oil-protein content and their relation with yield and evaluation of resistance for aerial blight and frog eye leaf spot diseases in soybean during kharif (July−December, 2019) at J.N.K.V.V., Jabalpur, Madhya Pradesh, India. The experiment was laid out using augmented block design with 154 genotypes of soybean including four check varieties namely JS 20-34, JS 20-98, JS 335 and NRC 86. Per cent disease severity was measured at peak of disease during seed formation stage (R5-R6). Yield and 100 seed weight were recorded at time of harvesting. Oil and protein content from harvested yield was estimated by using standard methods of association of official analytical chemists (AOAC). The results revealed that oil content varied from 16.8-20.2% and protein content from 36.1−41.2% in all 154 genotypes. Per plant average seed yield (3.9-15.1 g) and hundred seed weight (6.7−14.7 g) were also varied from genotypes to genotypes. The correlation between oil and protein was highly negative (r=-0.620**, p=0.01). This investigation identified ten genotypes with high oil (>20%) and fourteen genotypes with high protein (>40%) content. Among which JS 20-104, Cat 473B and RKS 24 were higher in protein, and Cat 48, Cat 330 and JS 20−69 were higher in oil content. In disease evaluation, eleven genotypes namely Cat 473B, Cat 60, Cat 642, JS 20−76, JSM 122, JSM 126A, JSM 126B, JSM 203, JSM 287, RKS 66 and SQL 89 exhibited dual resistance for aerial blight as well as frog eye leaf spot were screened out. The result showed that variation in oil-protein content and disease resistance depends on the genotype.